Abnormal head movement in a patient with tuberculous meningitis. (3rd October 2012) - Garg, Ravindra Kumar; Singh, Sunil Kumar; Malhotra, Hardeep Singh; Singh, Maneesh Kumar
Abstract : The bobble-head doll syndrome is characterised by abnormal head movements. These head movements are usually 'yes–yes' (up and down) type; rarely, head movements are 'no–no' (side-to-side) type. Commonly described causes of the bobble-head doll syndrome include third ventricular tumours, suprasellar arachnoid cysts, aqueductal stenosis and other lesions in the region of the third ventricle of the brain. We report a case of tuberculous meningitis with hydrocephalus; in this patient bobble-head doll syndrome developed following external ventricular drainage. In our patient, placement of intraventricular drain led to massive dilatation of the frontal horn of the left lateral ventricle because of blocked foramina of Monro on the left side. The bobble-head doll syndrome, presumably, developed because of the pressure effect of the dilated third ventricle on the dorsomedial nucleus of the thalamus, red nucleus and dentatorubrothalamic pathways. We think that distortion of the third ventricle was responsible for the impairment of the functions of all these structures.